Beyond the lungs: pulmonary embolism in a teenager with mycoplasma pneumoniae pneumonia - Supriya Adiody; Vishnu Narayanan S (The Egyptian Journal of Bronchology)
Abstract Mycoplasma pneumoniae, commonly referred to as Eaton’s agent, is a frequent respiratory pathogen capable of causing diseases that vary from mild infections of the upper respiratory system to serious cases of atypical pneumonia. Beyond respiratory involvement, this organism is associated with a broad range of non-respiratory complications, involving neurological, cardiac, hepatic, and hematological conditions, as well as polyarthritis and erythema multiforme. In this report, we report a rare case of Mycoplasma pneumoniae infection in a teenager, complicated by pulmonary thromboembolism. The purpose of reporting this article is to highlight the unexpected or rare occurrence of pulmonary embolism in a pediatric patient with Mycoplasma pneumoniae pneumonia, emphasizing the crucial need for prompt identification, precise diagnosis, and appropriate intervention of this unusual but potentially life-threatening complication, while contributing to the limited literature on Mycoplasma-associated thromboembolic events in children.